PENGARUH PENYAJIAN LAPORAN KEUANGAN DESA, LINGKUNGAN PENGENDALIAN DAN MORALITAS PERANGKAT TERHADAP POTENSI FRAUD DALAM PENGELOLAAN ALOKASI DANA DESA (Studi Kasus di Desa Sungai Golang Kecamatan Kelayang Kabupaten Indragiri Hulu) - Utami, Zulaikah Dwi; Sarwono, Aris Eddy; astuti, Dewi Saptantinah Puji (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
This study aims to analyze the direction of the village financial statements, the control environment and the morality of the device against the potential of fraud in the management of village fund allocation. The sampling technique uses census techniques. The sample of this study is 62 village devices in Sungai Golang village. Data collection using a questionnaire. Analysis of the data used is multiple linear regression analysis. The results showed that the of village financial statements had a negative effect on the potential for fraud in the management of village fund allocations, the control environment negatively affected the potential for fraud in the management of village fund allocations and the morality of negatively affected devices with potential fraud in managing village fund allocation.